PENINGKATAN KREATIVITAS MELALUI METODE PROYEK DI PAUD AISYIYAH BUSTHANUL ATFHAL 3 PONTIANAK TENGGARA - Alayinda, Alma; Ali, Muhammad; Yuniarni, Desni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research was carried out as an effort to improve the creativity of early childhood. The research problem is "Can the project method improve creativity in children aged 5-6 years in Aisyiyah Busthanul PAUD Atfhal 3 Southeast Pontianak?". This study uses descriptive methods in the form of classroom action research. Specifically, it can be concluded as follows: (1). Learning planning to improve the creativity of children aged 5-6 years through the project method in Aisyiyah Busthanul PAUD Atfhal 3 Southeast Pontianak which the teacher has made has been categorized as "good" (2). The implementation of learning to improve the creativity of children aged 5-6 years through the project method at Aisyiyah Busthanul PAUD Atfhal 3 Southeast Pontianak that the teacher has made has been categorized as "good" (3). There are differences in children's creativity before and after learning is done using the project method. In accordance with the results of the study, the following suggestions can be given: (1) Teachers should be able to consider methods in the learning process (2) Teachers should provide more learning media so that children are more free and creative (3) Teachers can explore methods that can improve children's creativity..Â Keywords: Enhancing Creativity, Through Project Methods